Produktivitas Kerja Pegawai Rumah Sakit - Eris Harismasakti; Dade Suparna (Universitas La Tansa Mashiro, 2014)
The purpose of this research was to examine empirically the effect between competency and motivation on work productivity among the employees at Regional General Hospital of Banten. The subjects of this research were 122 employees selected as samples by using proportionate stratified random sampling technique taken from the overall population of 175 employees. The data of each variable were collected separately by the respondents’ filling in a questionnaire. The effect technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the employees’ work productivity was positively affected by the competency and the motivation in Regional General Hospital of Banten, and the motivation was positively affected by the competency. The findings suggest that the variation of the work productivity of the employees might have been affected by the competency and the motivation.